PERUBAHAN ORIENTASI DALAM KEBIJAKAN BANTUAN PEMBANGUNAN RESMI JEPANG DI INDONESIA STUDI KASUS: BANTUAN KEMANUSIAAN PASCA TSUNAMI ACEH TAHUN 2004 DAN GEMPA BUMI YOGYAKARTA TAHUN 2006 - , Ratih Rachmawati; , Dra. Siti Daulah K, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Japanâs postwar reconstruction and reparations became the blueprint that Japan used to follow for its own Official Development Assistance (ODA) to Southeast Asia for economic and development purposes. ODA began to be controversial in its process of aid distribution. For those reason, in 2003 the Japanese government have revised Japanâs ODA Charter to resolve humanitarian issues. This thesis will examine why Japanese government choosing humanitarian issue to replace economic and development orientation. And how a new trend cooperation mechanism of transnational actors on implementation of ODA is being emerged, especially when Tsunami in Aceh and Earthquake in Yogyakarta. A spending strategy on The Disbursement Pattern of Japanâs ODA analysis predicts that Japan will continue to move toward based on humanitarian concern. It is useful for a good image of Japan. Gaining the Japanese public's understanding of ODA has become more crucial due to the prolonged and severe recession and the deterioration of government finances. Thus, humanitarian concern can be seen by new trend on Community-Based Development Concept and ODA schemes, namely Japan Disaster Relief Team and Dispatch of Senior Volunteers.